Implementasi Computer Based Test Pada SMP PGRI Se-Gugus V Kecamatan Cileungsi Kabupaten Bogor - Somantri; deshinta.arrovadewi; jelita.asian (Universitas Nusa Putra & Persatuan Insinyur Indonesia, 2023)
The importance of applying Information Technology in various sectors is a challenge for each institution, as well as in the education environment at the junior high school level, the application of Information Technology for evaluating learning activities as a measure of understanding of the learning material that has been obtained. Evaluation of learning at the junior high school level is usually carried out at least 2 (two) assessments, namely the Mid Semester Assessment (PTS) and the Year End Assessment (PAT). Within the Cileungsi branch of PGRI itself, it has 6 (six) working areas or clusters, namely Cluster I, Cluster II, Cluster III, Cluster IV and Cluster V, Cluster VI, in the implementation of this service it is carried out in Cluster V. At PGRI level Cluster V Kec. Cileungsi Kab. Bogor which houses 10 (ten) Junior High Schools (SMP) whose assessments still use paper-based tests (Paper Based Tests), but in accordance with the demands and needs of the implementation of the Computer Based Test (CBT) will be implemented for the first time in the implementation of the Mid Semester Assessment (PTS). ) ) Academic Year 2022/2023. The implementation of the Computer Based Test (CBT) has been carried out by PGRI Middle Schools in Cluster V, Kec. Bogor Cileungsi Regency has 8 (eight) schools, namely SMP PGRI Surya Kencana, SMP PGRI Klapanunggal, SMP PGRI Gandoang, SMP PGRI Bojong, SMP PGRI Jonggol, SMP PGRI Lulut, SMP PGRI Tanjungsari, SMP PGRI Sukamakmur with a total of 3,400 students. In its implementation using 2 (two) Servers and using laptops, computers and cellphones as clients used by participants and carried out for 6 (six) days.